AmdSYM, a new dominant recyclable marker cassette for Saccharomyces cerevisiae. Issue 1 (17th December 2012) - Solis‐Escalante, Daniel; Kuijpers, Niels G.A.; Bongaerts, Nadine; Bolat, Irina; Bosman, Lizanne; Pronk, Jack T.; Daran, Jean‐Marc; Daran‐Lapujade, Pascale
Abstract Despite the large collection of selectable marker genes available for Saccharomyces cerevisiae, marker availability can still present a hurdle when dozens of genetic manipulations are required. Recyclable markers, counterselectable cassettes that can be removed from the targeted genome after use, are therefore valuable assets in ambitious metabolic engineering programs. In the present work, the new recyclable dominant marker cassette amdSYM, formed by the Ashbya gossypii TEF2 promoter and terminator and a codon‐optimized acetamidase gene (Aspergillus nidulans amdS), is presented. The amdSYM cassette confers S. cerevisiae the ability to use acetamide as sole nitrogen source. Direct repeats flanking the amdS gene allow for its efficient recombinative excision. As previously demonstrated in filamentous fungi, loss of the amdS marker cassette from S. cerevisiae can be rapidly selected for by growth in the presence of fluoroacetamide. The amdSYM cassette can be used in different genetic backgrounds and represents the first counterselectable dominant marker gene cassette for use in S. cerevisiae. Furthermore, using astute cassette design, amdSYM excision can be performed without leaving a scar or heterologous sequences in the targeted genome. The present work therefore demonstrates that amdSYM is a useful addition to the genetic engineering toolbox for Saccharomyces laboratory, wild, and industrial strains.